(untitled) (International Journal of Biology and Chemistry, 2023)
The purpose of the study is the evaluation seeds diversity of different species in the genus Rhododendron after pre-sowing treatment with organic compounds. As the signs of the seeds diversity is understood the seed germination and the seedling height. The research was conducted at the B.M. Kozo-Polyansky Botanical Garden of Voronezh State University (geographic coordinates: E 39°12’, N 51°42’; 168.2 meters above sea level), Central Chernozem region (chernozem soil) in 2019-2020. It has been used ornamental shrubs. The study was made about the pyrimidinecarboxylic acids effect on the seed germination and the seedling height of Rhododendron species. The diversity of seeds is manifested in their heterogeneity according to morphological characteristics (the seedling height) and sowing qualities (seed germination) of Rhododendron species. The sowing properties (germinating capacity, seedling growth) were improved after treating the seeds with the organic compounds. There is the trend of increasing the seed germination and the seedling height of Rhododendron depended on the concentration of applied compounds. The seed germination for Rh. ledebourii, Rh. luteum, Rh. molle was increased from 5 to 7%, for Rh. schlippenbachii – from 5 to 10%. The seed treatment with pyrimidinecarboxylic acids at concentrations 0.01%, 0.05% and 0.1% allows to increase the seedling height for Rh. ledebourii from 37.5 to 75%, for Rh. luteum, Rh. molle - from 18.2 to 45.5%, for Rh. schlippenbachii from 20 to 40% concerning the control. To increase the seedling height, 2-benzylamino-4-methylpyrimidine-5-carboxylic acid at concentrations 0.05% and 0.1% is most effective. Morphologically close Rhododendron species (Rh. luteum, Rh. molle) indicated similar reactions to the seed treatment with compounds of the pyrimidinecarboxylic acid series.